Kinerja Sistem Pengolahan Air Limbah Domestik Terpusat Pada Kabupaten Padang Pariaman - Dalfi, Adi; Rita, Eva; Khadavi, Khadavi (Jurnal Ilmiah Rekayasa Sipil, 2025)
The national achievement of access to proper sanitation has not yet been achieved and is aligned with the Sustainable Development Goals (SDG's) target, one of which is "Realizing Access to Safe and Sustainable Drinking Water and Sanitation". In terms of accelerating the implementation of sanitation infrastructure in the regions, the Government conducts a financing program for the Construction of Centralized Domestic Wastewater Treatment Systems (SPALD-T). However, there are many obstacles and problems that cause the condition of infrastructure and facilities built to be not in an ideal condition, so it is necessary to analyze the performance of centralized domestic wastewater treatment systems, especially in Padang Pariaman Regency. The analysis was conducted in 11 (eleven) Nagari locations receiving community-based sanitation programs whose funds were sourced from DAK from 2019 to 2023 using descriptive qualitative methods, namely observation, interviews and documentation in the form of scoring and weighting and SWOT analysis. In the 11 Nagari analyzed, there is Nagari Sintuk in Sintuk Toboh Gadang District (program year 2022) which has a good quality assessment with a relative value of 8.25, while other Nagari get moderate and poor assessments. Based on the results of the analysis, the dominant aspect that determines the feasibility of waste management is the institutional management aspect in the 11 (eleven) villages analyzed. Where in the assessment of each aspect, the management institution aspect has a very low average value with a weight of 1.22. And based on the results of the SWOT analysis, the management organization of the Beneficiary Group (KPP) has a very important role in the sustainability of the community-based sanitation program.